THE IMPLEMENTATION OF AUTHENTIC ASSESSMENT IN MA DI PUTRA NURUL HAKIM IN THE ACADEMIC YEAR 2017/2018 - Imansyah, Imansyah; Utama, I Made Permadi; Sumarni, Baiq (Yavana Bhasha : Journal of English Language Education, 2018)
This research was conducted in attempt to analyze and describe the types ofauthentic assessment implemented by the EFL Teachers at MA DI PUTRA NURULHAKIM. This research applied a descriptive research designsince it was aimed at analyzingand describing the types of authentic assessment practiced by the EFL teachers in Englishclasses in MA DI PUTRA NURUL HAKIM. The method of gathering the data wasobservation supported with document study and interview to get more deeply. In relationto the problem raised, the current study found that there were various types of authenticassessment used by the EFL teachers. They were oral presentations and dramatizations,story telling, reading aloud,demonstration, constructed response items, writing samples,and peer assessment. The researcheralso found that the EFL teachers integrated one skillwith others since one single method of assessment can be used to assess more than one skill,and one skill was assessed by using some types of assessement